2020
DOI: 10.1016/j.ijcard.2020.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of same day discharge following elective left main stem percutaneous coronary intervention

Abstract: Background This study sought to investigate the safety and feasibility of same day discharge (SDD) practice and compare clinical outcomes to patients admitted for overnight stay (ON) undergoing elective left main stem (LMS) percutaneous coronary intervention (PCI). ON observation is still widely practiced in highly complex PCI as the standard of care, with no previous data comparing clinical outcomes in patients undergoing LMS PCI. Methods We analysed 6452 patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Even with the in creased anatomical and clinical complexity of PCIs in current practice (chronic coronary occlusion, left main coronary artery obstruction, multivessel disease), hospital discharge on the same day remains a feasible and safe strategy in most scenarios. 10,11 In our series, we noticed an increase in complexity of cases, demonstrated by an higher percentage of diabetic patients (28% versus 42%), greater number of bifurcation lesions (5% versus 15%), greater use of drug-eluting stents, and an increase in type B2 and C lesions (28% versus 46%), as shown in figure 2. These changes were not associated with an increase in adverse events.…”
Section: Discussionmentioning
confidence: 57%
“…Even with the in creased anatomical and clinical complexity of PCIs in current practice (chronic coronary occlusion, left main coronary artery obstruction, multivessel disease), hospital discharge on the same day remains a feasible and safe strategy in most scenarios. 10,11 In our series, we noticed an increase in complexity of cases, demonstrated by an higher percentage of diabetic patients (28% versus 42%), greater number of bifurcation lesions (5% versus 15%), greater use of drug-eluting stents, and an increase in type B2 and C lesions (28% versus 46%), as shown in figure 2. These changes were not associated with an increase in adverse events.…”
Section: Discussionmentioning
confidence: 57%
“…Patients with prognosis‐modifying lesions such as significant LM stenosis were more likely to undergo PCI instead of delayed CABG or no intervention at all. Delays in the safe reintroduction of cardiac surgery services due to insufficient COVID‐19 testing capacity, lack of bed availability and the resurgence in COVID‐19 case numbers, were likely to play a role in decision‐making regarding revascularisation strategy, with a shift towards LM PCI, which is associated with shorter length of stay and even a same day discharge, 26 to avoid further growth in CABG waiting lists. This is certainly in keeping with European Society of Cardiology guidance during the COVID‐19, which recommended Heart Team discussions on hybrid revascularisation (PCI and CABG) or full PCI for patients whose interventions cannot be postponed 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, acute stent thrombosis remains a nightmare of PCI, which is a great concern of cardiologists when considering the time to discharge patients. 8 Altogether, these factors incur additional risks to PCI patients, which may explain why they were less likely to be discharged on the same day. For IVUS, it is the most common imaging modality adopted in our center to guide the decision of stent deployment, particularly for those borderline and complex lesions involving left main artery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with complex PCI, left main artery involvement, two-stent bifurcation, complete total occlusion and atherectomy currently are not considered candidates for SDD in our center. We note that evidence supporting the safety of SDD for these high-risk patients is accumulating rapidly, 8 and these exclusion criteria may be lifted in the near future. We further found that the patient's age was not a significant predictor of SDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation